Phylogeography of the Spanish Moon Moth Graellsia isabellae (Lepidoptera, Saturniidae). Issue 1 (December 2016) - Marí-Mena, Neus; Lopez-Vaamonde, Carlos; Naveira, Horacio; Auger-Rozenberg, Marie-Anne; Vila, Marta
Abstract Background Geographic and demographic factors as well as specialisation to a new host-plant may lead to host-associated differentiation in plant-feeding insects. We explored the phylogeography of a protected moth, Graellsia isabellae, and its two recognised host-plant species (Pinus sylvestris andP. nigra ) in order to seek for any concordance useful to disentangle the evolutionary history of this iconic lepidopteran. Results DNA variation in one mitochondrial marker and nine nuclear microsatellite loci revealed a strong phylogeographic pattern across 28 populations ofG. isabellae studied in Spain and France comprising six groups mostly distributed along different mountain ranges. Reanalysis of a previously published chloroplast microsatellite dataset revealed a three and two-group structure for SpanishP. sylvestris andP. nigra, respectively. Overall, the population groupings of this protected moth did not match the ones ofP. sylvestris andP. nigra . Conclusions There was no evidence of host-associated differentiation between populations usingP. sylvestris and the ones inhabitingP. nigra . The two major mitochondrial clades ofG. isabellae likely diverged before the Last Glacial Maximum and geographically separated the species into a "southern" (Central and Southern Iberian clusters) and a "northern" lineage (Eastern Iberian, Pyrenean and French Alpine clusters). The Eastern Iberian System, where this insect uses both host-plants, harboured the highest level of genetic diversity. Such a group independently colonised the West and East parts of the Pyrenees. Our results point to a native origin for the French populations occurring in the Alps, genetically related to the Eastern Iberian and Pyrenean sites. The Central Iberian group derived from Southern Iberian ancestors. Secondary contacts were inferred between the Southern/Central Iberian populations and Eastern Iberian cluster as well as between the two Pyrenean ones. The mito-nuclear discordance observed with regard to the Eastern Iberian cluster is congruent with a secondary contact after the evolution of mito-nuclear incompatibilities in geographically isolated areas.